Associations of microvascular complications with all‐cause death in patients with diabetes and COVID‐19: The CORONADO, ABCD COVID‐19 UK national audit and AMERICADO study groups. Issue 1 (12th September 2022) - Hadjadj, Samy; Saulnier, Pierre‐Jean; Ruan, Yue; Zhu, Xu; Pekmezaris, Renee; Marre, Michel; Halimi, Jean Michel; Wargny, Matthieu; Rea, Rustam; Gourdy, Pierre; Cariou, Bertrand; Myers, Alyson K.; et al.
Abstract: Aim: To provide a detailled analysis of the microvascular burden in patients with diabetes hopitalized for COVD‐19. Materials and Methods: We analysed data from the French CORONADO initiative and the UK Association of British Clinical Diabetologists (ABCD) COVID‐19 audit, two nationwide multicentre studies, and the AMERICADO, a multicentre study conducted in New York area. We assessed the association between risk of all‐cause death during hospital stay and the following microvascular complications in patients with diabetes hospitalized for COVID‐19: diabetic retinopathy and/or diabetic kidney disease and/or history of diabetic foot ulcer. Results: Among 2951 CORONADO, 3387 ABCD COVID‐19 audit and 9327 AMERICADO participants, microvascular diabetic complications status was ascertained for 1314 (44.5%), 1809 (53.4%) and 7367 (79.0%) patients, respectively: 1010, 1059 and 1800, respectively, had ≥1 severe microvascular complication(s) and 304, 750 and 5567, respectively, were free of any complications. The patients with isolated diabetic kidney disease had an increased risk of all‐cause death during hospital stay: odds ratio [OR] 2.53 (95% confidence interval [CI] 1.66‐3.83), OR 1.24 (95% CI 1.00‐1.56) and OR 1.66 (95% CI 1.40‐1.95) in the CORONADO, the ABCD COVID‐19 national audit and the AMERICADO studies, respectively. After adjustment for age, sex, hypertension and cardiovascular disease (CVD), compared to those without microvascular complications, patients with microvascular complications had an increased risk of all‐cause death during hospital stay in the CORONADO, the ABCD COVID‐19 diabetes national audit and the AMERICADO studies: adjusted OR (adj OR) 2.57 (95% CI 1.69‐3.92), adj OR 1.22 (95% CI 1.00‐1.52) and adj OR 1.33 (95% CI 1.15‐1.53), respectively. In meta‐analysis of the three studies, compared to patients free of complications, those with microvascular complications had an unadjusted OR for all‐cause death during hospital stay of 2.05 (95% CI 1.42‐2.97), which decreased to 1.62 (95% CI 1.19‐2.119) after adjustment for age and sex, and to 1.50 (1.12‐2.02) after hypertension and CVD were further added to the model. Conclusion: Microvascular burden is associated with an increased risk of death in patients hospitalized for COVID‐19.